2013
DOI: 10.1002/jbm.a.34755
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate metal alloy type on the properties of hydroxyapatite coatings deposited using a novel ambient temperature deposition technique

Abstract: In addition to titanium grade 5, both cobalt chromium and stainless steel 316 were investigated. In this study HA coatings were deposited using both the CoBlast and plasma sprayed techniques, and the resultant HA coating and substrate properties were evaluated and compared. The CoBlast deposited HA coatings were found to present similar surface morphologies, interfacial properties and composition irrespective of the substrate alloy type. Coating thickness however displayed some variation with the substrate all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…In addition, the coated substrates showed promising results in vivo [589,590,592]. Similar results were obtained for the CoBlast TM process [592][593][594][595][596][597]. In addition, there is a shot peening deposition, which differs from the CoBlast TM process just by the nature of the blast medium (silica is used in shot peening, while alumina is used in CoBlast TM ) [598].…”
Section: Accepted Manuscriptsupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, the coated substrates showed promising results in vivo [589,590,592]. Similar results were obtained for the CoBlast TM process [592][593][594][595][596][597]. In addition, there is a shot peening deposition, which differs from the CoBlast TM process just by the nature of the blast medium (silica is used in shot peening, while alumina is used in CoBlast TM ) [598].…”
Section: Accepted Manuscriptsupporting
confidence: 80%
“…Therefore, an idea appeared to use this property to deposit CaPO 4 on metallic (Ti and its alloys) substrates [589][590][591][592][593][594][595][596][597]. The process was performed at room temperature using a sandblaster and either a HA powder only [589,590,592], or a mixture of a HA powder with a blast medium (a CoBlast TM process developed by ENBIO, Dublin, Ireland) [592][593][594][595][596][597].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Also Jouanny et al [65] reported that between the TiO 2 thin films deposited on the Si and Ti-6Al-4V substrate respectively, are differences from mechanical point of view. According to the studies reported by Barry et al [66] the nature of the substrate could influence the surface roughness and coating thickness but there are no significant differences between the interface properties and the coating composition depending on the type of alloy. Moreover, Ferraris et al [67] reported that the substrate also influences the biological properties of the samples.…”
Section: Resultsmentioning
confidence: 97%
“…However, serious drawbacks such as diffusion, fracturing, delamination from the base material caused by the thickness of the film and the difference of the coefficients of thermal expansion between the film of HAp and its substrate have been reported. 8,15,16 The thickness of commercially available plasma-spray coating is generally at least several tens of micrometers, and it is difficult to prepare a homogeneous HAp film in the nanometer range. 17 Therefore, many researchers have attempted to find an adequate material that can be made into a thin, dense film for surface treatment.…”
Section: Introductionmentioning
confidence: 99%